Mechanistic study of energy dependent scattering and hole-phonon interaction at hybrid polymer composite interfaces for optimized thermoelectric performance. (1st May 2019) - Lim, Khak Ho; Wong, Ka Wai; Cadavid, Doris; Liu, Yu; Zhang, Yu; Cabot, Andreu; Ng, Ka Ming
Abstract: Low energy barriers for charge transport may improve thermoelectric performance in heterostructured inorganic materials and hybrid polymer composites. In this study, earth abundant Cu12 Sb4 S13 nanoparticles were synthesized and incorporated into poly (3, 4-ethylenedioxythiophene) (PEDOT) matrices. The surface of nanoparticles was modified with ligands that improve carrier transport while maintaining the Seebeck coefficient. We demonstrated optimized thermoelectric figures of merit, ZT, were obtained at around 5 wt.% nanoparticle content, which we attribute to a low hole-phonon interaction, an effective phonon scattering, and mainly to the presence of a proper density of low energy barriers, 0.17 eV, between the energy states of Cu12 Sb4 S13 nanoparticle and PEDOT nanofiber and which selectively scatter low energy charge carriers. A 2.5-fold increase of ZT over pristine PEDOT nanofiber, ZT = 0.0098, was obtained by polymer composite at the optimal nanoparticle concentration. Remarkably, electrical conductivity and Seebeck coefficient decreased with an increase in nanoparticle content beyond 5 wt.%, which is attributed to the non-energy dependent hole-phonon interaction. These findings are expected to create an economical and new route for enhancing ZT in hybrid thermoelectric polymer composite and devices. Graphical abstract: Image 1